2022
DOI: 10.1016/j.scitotenv.2022.152919
|View full text |Cite
|
Sign up to set email alerts
|

Using highly stabilized digestate and digestate-derived ammonium sulphate to replace synthetic fertilizers: The effects on soil, environment, and crop production

Abstract: Recovered fertilizers (a highly stabilized digestate and ammonium sulphate) obtained from anaerobic digestion of sewage sludge, were used on plot trials with a maize crop, in a comparison with synthetic fertilizers. After three consecutive cropping seasons, the soils fertilized with the recovered fertilizers (RF), compared to those fertilized with synthetic fertilizers (SF), did not show significant differences either in their chemical characteristics or in the accumulation of inorganic and organic pollutants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…67 This represents an important revenue, especially when this scrubbing salt is part of the top priority materials in the RENURE frame, with many studies supporting its equivalent performance to that of synthetic N fertilizers. 69,70 As prices for synthetic fertilizers are increasing and nutrient resources are depleting, reusing valuable nutrients has enormous potential. So recycled fertilizers accompanied by the new EU Fertilizing Products Regulation (FPR) will guarantee the agronomic quality of EU-(biobased) fertilizer products while safeguarding environmental safety and human health.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…67 This represents an important revenue, especially when this scrubbing salt is part of the top priority materials in the RENURE frame, with many studies supporting its equivalent performance to that of synthetic N fertilizers. 69,70 As prices for synthetic fertilizers are increasing and nutrient resources are depleting, reusing valuable nutrients has enormous potential. So recycled fertilizers accompanied by the new EU Fertilizing Products Regulation (FPR) will guarantee the agronomic quality of EU-(biobased) fertilizer products while safeguarding environmental safety and human health.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Knowing that, a good quality ammonium sulfate (6%–7% N, 30% ammonium sulfate) can have an expected market value of 50–120 € tons –1 , , a price which is more than 10 times higher than that for N/K concentrates (1.2 € tons –1 ) . This represents an important revenue, especially when this scrubbing salt is part of the top priority materials in the RENURE frame, with many studies supporting its equivalent performance to that of synthetic N fertilizers. , …”
Section: Discussionmentioning
confidence: 99%
“…The findings align with those of Feng et al (2017), who reported an improved AD process with increased biomethane yield using a serial continuous stirred tank reactors AD process in a co-digestion set up with meadow grass. The enhanced degradation of the organic matter by an extended AD stabilises the digestates in addition to the improved fertiliser value, reducing possible residual methane potential during storage and application (Nyang'au et al, 2022;Zilio et al, 2022).…”
Section: Tablementioning
confidence: 99%
“…GWP values varied between 0.08 and 0.35 kg CO 2 eq kg − 1 N and are hence low as compared to values obtained from long-term field studies. Over ten months, Zilio et al (2022) measured net N 2 O cum emissions between 1.2 and 3 % of N applied, from digestate + AS and urea + AS fertilised fields, corresponding to 3.80 and 9.84 kg CO 2 eq kg − 1 N, respectively. The authors concluded that the environmental impact in terms of GHG emissions from fertilisation with the tested BBFs or urea were comparable, in agreement with findings from our study.…”
Section: Global Warming Potentialmentioning
confidence: 99%